How to Deal with the Risks of Phasing out Coal in Germany through National Carbon Pricing - Sebastian Osorio; Robert C. Pietzcker; Michael Pahle; Ottmar Edenhofer (Center for Economic Studies and ifo Institute (CESifo), 2018)
Germany aims to phase out coal to achieve its 2030 climate target, for which a UK-style carbon price floor is considered. But this measure comes with risks related to the uncertainty about what price level is sufficient, and the waterbed effect arising from unilateral policy under the EU-ETS. Quantifying these risks we find that to be on the “safe side” target-wise, the price must be nearly twice as high as the reference scenario price (33 exteuro/tCO2). Further, cancelling 1.1 GtCO2 of certificates and forming coalitions with other countries is essential to reduce the risk that EU climate policy will renationalize.
Keywords: L94; Q58; 330; EU-ETS; carbon price floor; coal phase-out; policy interaction; waterbed effect